The Role of Optimism in Reducing Psychological Distress Amongst Women in Urban Areas - Hanisha Garg (International Journal of Trends in Humanities, 2025)
This paper aims to explore the role of optimism in reducing psychological distress among women living in urban areas. Psychological distress, encompassing anxiety, depression, and chronic stress, has become increasingly prevalent due to the fast-paced and demanding nature of urban life. Women, in particular, face unique stressors including work-life imbalances, financial pressures, safety concerns, and societal expectations, which contribute significantly to elevated levels of mental strain. Finding healthy coping strategies is essential for fostering mental health as urbanization continues to change lifestyles. The study adopted a quantitative research methodology, using standardized psychological scales to measure levels of optimism and psychological distress among a sample of urban women. Statistical analysis revealed a significant negative correlation between optimism and psychological distress, indicating that higher levels of optimism are associated with lower levels of anxiety, depression, and stress. The findings draw upon theoretical perspectives such as Positive Psychology Theory, which emphasizes the role of optimism in fostering emotional well-being, Resilience Theory, which illustrates how optimistic individuals better navigate adversity, and Cognitive Appraisal Theory, which explains how optimistic appraisal of stressors leads to more adaptive coping. In conclusion, the study highlights optimism as a key protective factor against psychological distress and underscores the need for interventions that cultivate optimistic thinking in urban women to enhance their mental health and resilience in high-stress environments.
Keywords: Community Based Approach; Mental well-being; Optimism; Urban Women; Urbanization and stress; psychological distress